Medical glass container
Crystallized glass containers with optimized Li2O-Al2O3-SiO2 composition provide enhanced hydrolysis and thermal shock resistance, addressing the limitations of standard pharmaceutical glass by ensuring stability and transparency for chemically unstable medicinal solutions.
Patent Information
- Application Number
- JP2024182478
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-03-12
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2039-12-19
AI Technical Summary
Pharmaceutical glass containers face challenges with insufficient hydrolysis resistance, especially when handling chemically unstable and reactive medicinal solutions, and require improved thermal shock resistance and transparency to prevent drug deterioration.
The development of crystallized glass containers, specifically composed of Li2O-Al2O3-SiO2 with β-quartz solid solution as the main crystal, offering enhanced hydrolysis resistance, thermal shock resistance, and transparency by controlling the glass composition to optimize thermal expansion and chemical resistance.
The crystallized glass containers exhibit superior hydrolysis resistance, thermal shock resistance, and transparency, ensuring the stability and quality of chemically unstable medicinal solutions, while maintaining transparency to block UV rays and prevent drug deterioration.
Smart Images

Figure 2025003525000001 
Figure 2025003525000002 
Figure 2025003525000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pharmaceutical glass container. [Background technology]
[0002] Pharmaceutical glass containers such as vials and ampoules are required to have the following properties: (a) The components in the filled chemical solution do not react with the components in the glass. (b) High hydrolysis resistance so as not to contaminate the filled chemicals, and high hydrolysis resistance must be maintained even after various heat treatments during container processing. (c) A low coefficient of thermal expansion so that damage caused by thermal shock is unlikely to occur during the manufacturing process of glass tubes and during processing into vials, ampoules, etc.
[0003] Standard pharmaceutical glass containers that meet these required properties are generally made from borosilicate glass. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2014-214084 Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, the development of chemical solutions to be filled has progressed, and chemical solutions with higher efficacy are being used. Some of these chemical solutions are chemically unstable, easily denatured, and highly reactive with glass. As a result, glass with higher hydrolysis resistance than ever before is required.
[0006] Patent Document 1 proposes glass in which the amount of K2O added is adjusted in order to improve hydrolysis resistance, but there is a problem in that the hydrolysis resistance is still insufficient.
[0007] An object of the present invention is to provide a medical glass container having excellent hydrolysis resistance. [Means for solving the problem]
[0008] As a result of various experiments, the present inventors have found that crystallized glass is more excellent in hydrolysis resistance than amorphous glass such as borosilicate glass.
[0009] That is, the pharmaceutical glass container of the present invention is characterized in that it is made of crystallized glass.
[0010] The pharmaceutical glass container of the present invention preferably consumes 0.50 mL or less of 0.01 mol / L hydrochloric acid per 100 mL of dissolution solution in a hydrolysis resistance test according to ISO 4802-1 (1988).
[0011] In the medical glass container of the present invention, the crystallized glass is preferably Li2O-Al2O3-SiO2 crystallized glass.
[0012] In the pharmaceutical glass container of the present invention, it is preferable that β-quartz solid solution is precipitated as the main crystal in the crystallized glass, which makes it easy to obtain a pharmaceutical glass container having a low thermal expansion coefficient and high transmittance.
[0013] In the medical glass container of the present invention, the crystallized glass preferably contains, by weight, 40-75% SiO2, 6-30% Al2O3, and 0.1-10% Li2O.
[0014] The medical glass container of the present invention preferably has a Young's modulus of 60 GPa or more.
[0015] The pharmaceutical glass container of the present invention has a thermal expansion coefficient of 20×10 at 30 to 380° C. -7 / ° C. or less. In this way, it becomes easy to obtain a medical glass container with excellent thermal shock resistance.
[0016] The pharmaceutical glass container of the present invention preferably has a thickness of 1 mm and an average transmittance of 65% or more at wavelengths of 400 to 800 nm.
[0017] The pharmaceutical glass container of the present invention preferably has a thickness of 1 mm and a transmittance of 60% or less at a wavelength of 350 nm, which makes it easier to block ultraviolet rays that may cause deterioration of medicines.
[0018] The pharmaceutical glass container of the present invention has a weight loss per unit area ρ of 75 mg / dm2 or less in an alkali resistance test according to ISO 695 (1991). 2 It is preferable that:
[0019] The pharmaceutical glass container of the present invention has a weight ratio of SiO2 / (Li2O+Na2O+K2O+MgO+CaO+SrO+BaO) of 3 or more, and the sum of half the weight loss per unit area S in an acid resistance test in accordance with YBB00342004-2015 and the weight loss per unit area ρ in an alkali resistance test in accordance with ISO 695 (1991) is 70 mg / dm 2 The pharmaceutical glass container of the present invention is characterized by the following. Since the pharmaceutical glass container of the present invention has excellent acid resistance and alkali resistance, it can be used for medicinal solutions with a wide range of pH. Although quartz glass has excellent acid resistance and alkali resistance, it is difficult to process it into complex shapes of pharmaceutical containers such as vials, ampoules, and syringes. Here, SiO2 / (Li2O+Na2O+K2O+MgO+CaO+SrO+BaO) is the value obtained by dividing the content of SiO2 by the total amount of Li2O, Na2O, K2O, MgO, CaO, SrO, and BaO.
[0020] The method for producing a medical glass container of the present invention is characterized in that after a glass tube is processed to obtain a glass container, the glass container is heat-treated to crystallize it. Effect of the Invention
[0021] According to the present invention, it is possible to provide a medical glass container having excellent hydrolysis resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The pharmaceutical glass container of the present invention is characterized by being made of crystallized glass, and preferably consumes 0.50 mL or less of 0.01 mol / L hydrochloric acid per 100 mL of dissolution solution in a hydrolysis resistance test according to ISO 4802-1 (1988).
[0023] First, the crystallized glass used in the present invention will be described.
[0024] The crystallized glass is preferably Li2O-Al2O3-SiO2 crystallized glass, and more preferably contains, by weight, 40-75% SiO2, 6-30% Al2O3, and 0.1-10% Li2O. The reasons for limiting the composition as above are as follows. In the following description of the content of each component, "%" means "weight %" unless otherwise specified.
[0025] SiO2 is a component that forms the skeleton of glass and constitutes Li2O-Al2O3-SiO2 crystals. If the content of SiO2 is too high, the meltability of glass decreases, the viscosity of the glass melt increases, making it difficult to clarify and mold the glass, and productivity tends to decrease. Therefore, the content of SiO2 is preferably 75% or less, 74% or less, 73% or less, 70% or less, or 69% or less. On the other hand, if the content of SiO2 is too low, the thermal expansion coefficient tends to be high, making it difficult to obtain crystallized glass with excellent thermal shock resistance. In addition, the hydrolysis resistance, alkali resistance, and acid resistance tend to decrease. Therefore, the content of SiO2 is preferably 40% or more, 45% or more, 50% or more, 55% or more, 60% or more, 64% or more, or 65% or more.
[0026] Al2O3 forms the skeleton of the glass and is a component that constitutes Li2O-Al2O3-SiO2 crystals. The content of Al2O3 is preferably 6-30%, 10-30%, 12-29%, 13-28%, and particularly 15-28%. If the content of Al2O3 is too low, the thermal expansion coefficient tends to be high, making it difficult to obtain crystallized glass with excellent thermal shock resistance. In addition, the crystallization degree tends to be low and the glass tends to become cloudy, making it difficult to check insoluble foreign matter inside the container. Furthermore, hydrolysis resistance tends to decrease. On the other hand, if the content of Al2O3 is too high, the meltability of the glass decreases, the viscosity of the glass melt increases, making it difficult to clarify, and mullite crystals are easily precipitated, making it difficult to mold the glass into devitrified glass, and productivity tends to decrease.
[0027] Li2O is a component that constitutes Li2O-Al2O3-SiO2 crystals, and has a large effect on the crystallinity, and also reduces the viscosity of the glass, improving the meltability and formability of the glass. The content of Li2O is preferably 0.1-10%, 0.5-8%, 1-7%, 1-6%, and particularly 1-5%. If the content of Li2O is too small, mullite crystals tend to precipitate and the glass tends to devitrify. In addition, when crystallizing the glass, Li2O-Al2O3-SiO2 crystals are difficult to precipitate, making it difficult to obtain crystallized glass with excellent hydrolysis resistance, alkali resistance, and acid resistance. Furthermore, the meltability of the glass decreases, the viscosity of the glass melt increases, making it difficult to clarify the glass, and making it difficult to mold the glass, which tends to reduce productivity. On the other hand, if the content of Li2O is too high, the crystallinity becomes too strong, and the glass tends to devitrify and the transmittance decreases, making it difficult to check insoluble foreign matter inside the container.
[0028] Al2O3 / Li2O is preferably 1 to 10, 1.5 to 9, 2 to 8, 2.5 to 7, 3 to 6, and particularly preferably 4 to 6. If Al2O3 / Li2O is too small, Li2O-Al2O3-SiO2 crystals are difficult to precipitate, and the glass tends to become cloudy and have low transmittance. On the other hand, if the molar ratio of Al2O3 / Li2O is too large, Li2O-Al2O3-SiO2 crystals are difficult to precipitate, and the glass tends to become cloudy and have low transmittance. In addition, the hydrolysis resistance, alkali resistance, and acid resistance of the crystallized glass tend to decrease. Note that "Al2O3 / Li2O" is the value obtained by dividing the content of Al2O3 by the content of Li2O.
[0029] SiO2 / Li2O is preferably 5 to 20, 8 to 19, and particularly 10 to 18. If SiO2 / Li2O is too small, Li2O-Al2O3-SiO2 crystals are difficult to precipitate, and the glass tends to become cloudy and have low transmittance. In addition, the glass matrix increases, so the hydrolysis resistance, alkali resistance, and acid resistance of the crystallized glass may decrease. On the other hand, if SiO2 / Li2O is too large, Li2O-Al2O3-SiO2 crystals are difficult to precipitate, and the glass tends to become cloudy and have low transmittance. In addition, the viscosity of the glass melt increases, and meltability and moldability decrease, which makes it easy for productivity to decrease. Note that "SiO2 / Li2O" is the value obtained by dividing the content of SiO2 by the content of Li2O.
[0030] SiO2 / Al2O3 is preferably 1 to 7, 1.5 to 6, 2 to 5, 2.2 to 4, and particularly preferably 2.5 to 3.5. If SiO2 / Al2O3 is too small or too large, Li2O-Al2O3-SiO2 crystals are difficult to precipitate, and the hydrolysis resistance, alkali resistance, and acid resistance of the crystallized glass tend to decrease. Note that "SiO2 / Al2O3" is the value obtained by dividing the SiO2 content by the Al2O3 content.
[0031] The crystallized glass used in the present invention may contain the following components in addition to the above components in the glass composition.
[0032] Na2O is a component that reduces the viscosity of glass and improves the melting and moldability of glass. The content of Na2O is preferably 0-10%, 0-5%, 0-4%, 0-3%, 0-2%, 0.1-1.5%, 0.1-1%, 0.1-0.8%, and particularly preferably 0.1-0.5%. Na2O is a component that is difficult to dissolve in Li2O-Al2O3-SiO2 crystals, and is likely to remain in the glass matrix after crystallization. Therefore, if the content of Na2O is too high, the hydrolysis resistance, acid resistance, and alkali resistance of the crystallized glass tend to decrease.
[0033] K2O is a component that reduces the viscosity of glass and improves the melting and moldability of glass. The content of K2O is preferably 0-10%, 0-5%, 0-4%, 0-3%, 0-2%, 0.1-1.5%, 0.1-1%, 0.1-0.8%, and particularly preferably 0.1-0.5%. K2O is a component that is difficult to dissolve in Li2O-Al2O3-SiO2 crystals, and tends to remain in the glass matrix after crystallization. Therefore, if the content of K2O is too high, the hydrolysis resistance, acid resistance, and alkali resistance of the crystallized glass tend to decrease.
[0034] MgO is a component that dissolves in Li2O-Al2O3-SiO2 crystals and adjusts the thermal expansion coefficient of Li2O-Al2O3-SiO2 crystals. It also reduces the viscosity of glass to improve meltability and moldability. The content of MgO is preferably 0-10%, 0-5%, or 0-3%, and is particularly preferably not contained. If the content of MgO is too high, it becomes difficult to dissolve in Li2O-Al2O3-SiO2 crystals and tends to remain in the glass matrix after crystallization. Therefore, the hydrolysis resistance, acid resistance, and alkali resistance of the crystallized glass tend to decrease. In addition, since the difference in the thermal expansion coefficient between the glass matrix and the crystals tends to be large, there is a risk of breakage during the crystallization process. Furthermore, scattered light is easily generated due to the difference in refractive index between the glass matrix and the crystals. As a result, the transmittance of the crystallized glass decreases, making it difficult to check insoluble foreign matter inside the container.
[0035] CaO is a component that reduces the viscosity of glass and improves the melting and moldability of glass. The content of CaO is preferably 0-10%, 0-5%, 0-3%, or 0-1%, and is particularly preferably not contained. CaO is a component that is difficult to dissolve in Li2O-Al2O3-SiO2 crystals, and is likely to remain in the glass matrix after crystallization. Therefore, if the CaO content is too high, the hydrolysis resistance, acid resistance, and alkali resistance of the crystallized glass tend to decrease. In addition, there is a tendency for heterogeneous crystals to precipitate during the crystallization process, and scattered light is likely to occur due to the refractive index difference between the heterogeneous crystals and the Li2O-Al2O3-SiO2 crystals. As a result, the transmittance of the crystallized glass tends to decrease.
[0036] SrO is a component that reduces the viscosity of glass and improves the melting and moldability of glass. The content of SrO is preferably 0-10%, 0-5%, 0-3%, or 0-1%, and is particularly preferably not contained. If the content of SrO is too high, the glass is easily devitrified and easily broken. SrO is a component that is difficult to dissolve in Li2O-Al2O3-SiO2 crystals, and is likely to remain in the glass matrix after crystallization. Therefore, if the content of SrO is too high, the hydrolysis resistance, acid resistance, and alkali resistance of the crystallized glass tend to decrease. In addition, scattered light is easily generated due to the refractive index difference between the glass matrix and the crystals. As a result, the transmittance of the crystallized glass decreases, making it difficult to check insoluble foreign matter inside the container.
[0037] BaO is a component that reduces the viscosity of glass and improves the melting and moldability of glass. The content of BaO is preferably 0-10%, 0-5%, 0-4%, or none. BaO is a component that is difficult to dissolve in Li2O-Al2O3-SiO2 crystals, and is likely to remain in the glass matrix after crystallization. Therefore, if the content of BaO is too high, the hydrolysis resistance, acid resistance, and alkali resistance of the crystallized glass tend to decrease. In addition, scattered light is likely to occur due to the refractive index difference between the glass matrix and the crystals. As a result, the transmittance of the crystallized glass decreases, making it difficult to check insoluble foreign matter inside the container. Furthermore, when a chemical solution containing sulfate is filled and stored in a glass container, BaO in the glass matrix may dissolve into the chemical solution and generate barium sulfate crystals, which may become insoluble foreign matter.
[0038] In addition, the weight ratio of SiO2 / (Li2O+Na2O+K2O+MgO+CaO+SrO+BaO) is preferably 3 or more, 4 or more, 6 or more, 9 or more, 10 or more, 11 or more, and particularly preferably 12 or more. If SiO2 / (Li2O+Na2O+K2O+MgO+CaO+SrO+BaO) is too small, the acid resistance and hydrolysis resistance are likely to decrease. On the other hand, if SiO2 / (Li2O+Na2O+K2O+MgO+CaO+SrO+BaO) is too large, the solubility is likely to decrease. Therefore, it is preferable that SiO2 / (Li2O+Na2O+K2O+MgO+CaO+SrO+BaO) is 33 or less, 30 or less, 25 or less, 20 or less, and particularly preferably 18 or less.
[0039] ZnO is a component that dissolves in Li2O-Al2O3-SiO2 crystals and has a large effect on crystallinity. The content of ZnO is preferably 0-10%, 0-5%, 0-3%, or 0-1%, and is particularly preferably zero. If the content of ZnO is too high, the crystallinity becomes too strong, making the glass prone to devitrification, decreasing the transmittance of the crystallized glass, and making it difficult to check for insoluble foreign matter inside the container.
[0040] P2O5 is a component that suppresses the precipitation of coarse ZrO2 crystals. When coarse crystals are precipitated, scattered light is likely to occur. As a result, the transmittance of the crystallized glass decreases, making it difficult to check insoluble foreign matter inside the container. The content of P2O5 is preferably 0-5%, 0-4%, or 0-3%, and is particularly preferably zero. If the content of P2O5 is too high, the amount of precipitation of Li2O-Al2O3-SiO2 crystals decreases, and the thermal expansion coefficient tends to increase. In addition, the hydrolysis resistance, acid resistance, and alkali resistance of the crystallized glass tend to decrease.
[0041] TiO2 is a component that acts as a nucleating agent for precipitating crystals in the crystallization process. On the other hand, if a large amount is contained, it is also a component that significantly intensifies the coloring of the glass. The TiO2 content is preferably 0 to 8%, 0 to 7%, 0.5 to 5%, and particularly preferably 1 to 5%. If the TiO2 content is too high, the coloring of the glass tends to be intensified.
[0042] ZrO2 is a nucleation component for precipitating crystals in the crystallization process. The content of ZrO2 is preferably 0 to 8%, 0 to 5%, 0.5 to 5%, and particularly preferably 1 to 5%. If the content of ZrO2 is too high, coarse ZrO2 crystals are precipitated, which makes the glass more susceptible to devitrification and breakage.
[0043] SnO2 is a component that acts as a fining agent. The content of SnO2 is preferably 0 to 3%, 0.001 to 2%, 0.005 to 1%, 0.003 to 0.7%, and particularly preferably 0.01 to 0.5%. If the content of SnO2 is too high, the coloring of the glass tends to become stronger.
[0044] In addition, As2O3, Sb2O3, Cl, F, Na2SO4, etc. may be contained as fining agents other than SnO2. The total content of these fining agents is preferably 1.5% or less, 1% or less, 0.7% or less, and particularly preferably 0.5% or less. These fining agents may be used alone or in combination.
[0045] B2O3 is a component that promotes the crystal transformation from β-quartz solid solution to β-spodumene solid solution. When β-quartz solid solution transforms into β-spodumene, the glass becomes more susceptible to breakage due to the increase in the local thermal expansion coefficient caused by the precipitation of β-spodumene. For this reason, it is preferable that the glass does not substantially contain B2O3 (specifically, less than 0.05%).
[0046] Fe2O3 is a component that enhances the coloring of glass. The content of Fe2O3 is preferably 0 to 0.15%, 0.003 to 0.04%, and particularly preferably 0.003 to 0.03%. If the content of Fe2O3 is too high, the coloring of the glass tends to be intensified. The lower the content of Fe2O3, the more preferable it is because coloring can be suppressed, but in order to keep the content below 0.003%, for example, it is necessary to use expensive high-purity raw materials, which increases the manufacturing cost.
[0047] In the crystallized glass having the above composition, β-quartz solid solution is easily precipitated. If β-quartz solid solution is precipitated as the main crystal, the crystallized glass can easily transmit visible light and has high transparency. It also becomes easy to reduce the thermal expansion coefficient of the glass.
[0048] In the hydrolysis resistance test according to ISO 4802-1 (1988), the pharmaceutical glass container of the present invention preferably consumes 0.01 mol / L hydrochloric acid per 100 mL of dissolution solution at 0.50 mL or less, 0.45 mL or less, and particularly preferably consumes 0.40 mL or less, and in the hydrolysis resistance test according to ISO 720 (1985), the pharmaceutical glass container preferably consumes 0.02 mol / L hydrochloric acid per 1 g of glass powder at 0.1 mL or less, 0.08 mL or less, 0.06 mL or less, 0.04 mL or less, and particularly preferably consumes 0.03 mL or less. If the hydrochloric acid consumption is too high, when a pharmaceutical glass container is filled with a pharmaceutical solution and stored, the dissolution of glass components, especially alkali components, may increase significantly, causing deterioration of the pharmaceutical solution components.
[0049] The Young's modulus of the pharmaceutical glass container of the present invention is preferably 60 GPa or more, 65 GPa or more, particularly 70 GPa or more. If the Young's modulus is too small, the thermal shock resistance is likely to decrease. The upper limit of the Young's modulus is not particularly limited, but is practically 300 GPa or less.
[0050] The pharmaceutical glass container of the present invention has a thermal expansion coefficient of 20×10 -7 / ℃ or less, 15×10 -7 / ℃ or less, 10×10 -7 / ℃ or less, 7×10 -7 / ℃ or less, 5×10 -7 / ℃ or less, especially 2×10 -7 / °C or less. In cases where thermal shock resistance is particularly required, it is preferable that the -7 / ℃~5×10 -7 / ℃, -2.5×10 -7 / ℃~2.5×10 -7 / ℃, especially -2×10 -7 / ℃~2×10 -7 / °C.
[0051] Since it is necessary to check for insoluble foreign matter inside the container, the pharmaceutical glass container of the present invention preferably has a transparent appearance, and specifically, the average transmittance at a thickness of 1 mm and a wavelength of 400 to 800 nm is preferably 65% or more, 68% or more, and particularly preferably 70% or more. If the average transmittance in the wavelength range is too low, the pharmaceutical glass container will be too strongly colored and transparency will be easily reduced.
[0052] The pharmaceutical glass container of the present invention preferably has a thickness of 1 mm and a transmittance at a wavelength of 350 nm of 60% or less, 50% or less, 45% or less, particularly 40% or less. If the transmittance at this wavelength is too high, it becomes difficult to block ultraviolet rays that may cause deterioration of medicines.
[0053] The pharmaceutical glass container of the present invention has a weight loss per unit area ρ of 75 mg / dm2 or less in an alkali resistance test according to ISO 695 (1991). 2 Below, 70mg / dm2 Below 65 mg / dm 2 If the weight loss amount ρ is too large, there is a risk of causing deterioration in the quality of the drug filled inside.
[0054] In the acid resistance test according to YBB00342004-2015, the pharmaceutical glass container of the present invention has a half weight loss per unit area S of 10 mg / dm 2 Below, 8mg / dm 2 Below 6 mg / dm 2 If the half weight loss amount S is too large, there is a risk of the quality of the drug filled inside being deteriorated.
[0055] In addition, the sum of half the weight loss per unit area S in the acid resistance test conforming to YBB00342004-2015 and the weight loss per unit area ρ in the alkali resistance test conforming to ISO 695 (1991) is 70 mg / dm 2 Below 60mg / dm 2 Below, 50mg / dm 2 Below, 45mg / dm 2 Below, 40mg / dm 2 Below, 35mg / dm 2 Below 30 mg / dm 2 In this way, it is possible to further improve the acid resistance and alkali resistance.
[0056] The shape of the pharmaceutical glass container of the present invention is not particularly limited, and may be a container shape having a bottom surface or a tubular shape having no bottom surface.
[0057] Next, a method for producing the pharmaceutical glass container of the present invention will be described. The following description is an example using the Danner method. However, the method is not limited to the Danner method, and any conventionally known method such as the Vello method or the down-draw method may be used for production.
[0058] First, the glass raw materials are mixed to produce a glass batch so as to obtain the above glass composition. Then, the glass batch is continuously fed into a melting furnace at 1550 to 1700°C to melt and clarify, and the obtained molten glass is wound around a rotating refractory while air is blown out from the tip of the refractory, and the glass is drawn out in a tubular shape from the tip and cooled to obtain a glass tube. The obtained glass tube is cut to a predetermined length and processed to obtain a glass container.
[0059] Next, the obtained glass container is heat-treated to crystallize. As for the crystallization conditions, first, nucleation is performed at 700 to 950°C (preferably 730 to 900°C) for 6 to 300 minutes (preferably 10 to 180 minutes), and then crystal growth is performed at 800 to 1050°C (preferably 800 to 1000°C) for 6 to 600 minutes (preferably 10 to 300 minutes). In this way, a transparent medical glass container in which β-quartz solid solution crystals are precipitated as the main crystals can be obtained. Note that if the nucleation temperature or crystal growth temperature is too low and / or the nucleation time or crystal growth time is too short, crystals are difficult to precipitate. Also, if the nucleation temperature or crystal growth temperature is too high and / or the nucleation time or crystal growth time is too long, β-spodumene solid solution tends to precipitate, and the crystals become coarse, so that the transmittance tends to decrease. EXAMPLES
[0060] Example 1 The present invention will be described below based on examples, but the present invention is not limited to these examples. Tables 1 and 2 show examples of the present invention and comparative examples.
[0061] [Table 1]
[0062] [Table 2]
[0063] The pharmaceutical glass containers of the examples were produced as follows. Raw materials were prepared and mixed to obtain glass having the composition shown in Tables 1 and 2, to obtain a raw material batch. This raw material batch was continuously charged into a melting furnace at 1600 to 1680°C to melt and clarify, and the obtained molten glass was then wound around a rotating refractory while air was blown out from the tip of the refractory, and the glass was drawn out from the tip in a tubular shape and cooled to obtain a glass tube with an outer diameter of 12 to 15 mmφ. The obtained glass tube was cut to a length of 160 to 300 mm, and one end of the glass tube was melt-sealed with a burner to obtain a glass container (glass container before crystallization) with a length of 80 to 150 mm.
[0064] The glass container was heat-treated at 730-780°C for 5-180 minutes to form nuclei, and then further heat-treated at 870-920°C for 5-60 minutes to grow crystals, yielding a pharmaceutical glass container. The resulting pharmaceutical glass container (glass container after crystallization) was evaluated for precipitated crystals, hydrolysis resistance, alkali resistance, acid resistance, Young's modulus, thermal expansion coefficient, average transmittance at wavelengths of 400-800 nm, and transmittance at a wavelength of 350 nm. The results are shown in Tables 1 and 2.
[0065] The precipitated crystals were evaluated using an X-ray diffractometer (Rigaku Corporation, fully automatic multipurpose horizontal X-ray diffractometer Smart Lab).
[0066] The hydrolysis resistance was evaluated by the hydrolysis resistance test method according to ISO 4802-1 (1988) and the hydrolysis resistance test method according to ISO 720 (1985). The detailed test procedures are as follows.
[0067] (ISO 4802-1(1988)) The inner and outer surfaces of the glass container obtained in the example were washed with purified water. The glass container was filled with purified water (10.6 mL) equivalent to 90% of the total volume of the glass container. The mouth of the glass container was covered with aluminum foil and secured with a rubber band. The glass container containing purified water was placed in an autoclave, and the temperature was raised from room temperature to 100°C, and then heated from 100°C to 121°C at a heating rate of 1°C / min. After reaching 121°C, the container was held for 60 minutes and further cooled to 100°C at 0.5°C / min. The glass container was then removed from the autoclave and placed in a tray containing purified water to cool to room temperature. After cooling, the eluate (10 mL) in the glass container was transferred to a 200 mL conical beaker. The same operation was performed five times using five glass containers obtained in the same manner as in the example to obtain 50 mL of eluate. Using a volumetric pipette, 25 mL of the eluate was taken and transferred to two 50 mL conical beakers. Similarly, 25 mL of the blank was taken from 50 mL of purified water using a volumetric pipette and transferred to two 50 mL conical beakers. 50 μL of methyl red indicator was added to the eluate and blank. A burette was filled with 0.01 mol / L hydrochloric acid, and neutralization titration was performed on 25 mL of the eluate. The amount of hydrochloric acid consumed when the color of the eluate became the same as the color of the blank was recorded. The test was performed with n=2, and the average value was calculated, and then the amount of hydrochloric acid consumed per 100 mL of eluate was calculated.
[0068] (ISO 720(1985)) The inner and outer surfaces of the glass container obtained in the example were thoroughly wiped with ethanol, and the sample was crushed with an alumina mortar and pestle, and then classified using three stainless steel sieves with openings of 710 μm, 425 μm, and 300 μm. The glass powder remaining on the 300 μm sieve was collected, and the glass remaining on the 700 μm and 425 μm sieves was crushed again. The same operation was repeated until the amount of glass powder on the 300 μm sieve was 10 g or more. The sample powder remaining on the 300 μm sieve was transferred to a beaker, 30 mL of acetone was poured, and ultrasonic cleaning was performed for 1 minute. The supernatant liquid was discarded, and the same operation was repeated four times. Then, 30 mL of acetone was poured into the beaker, and the operation of gently shaking it with hands and discarding only the supernatant liquid was repeated three times. The mouth of the beaker was covered with aluminum foil, several holes were made, and the beaker was dried in an oven at 110 ° C for 30 minutes. After that, it was taken out and cooled in a desiccator for 30 minutes. The obtained sample powder was weighed to 10g ± 0.0001g using an electronic balance, placed in a 250mL flask, and 50mL of ultrapure water was added. A flask filled with only 50mL of ultrapure water was also prepared as a blank. The mouth of the flask was sealed with a quartz container, placed in an autoclave, and heat-treated at 121°C for 30 minutes. At this time, the temperature was raised from 100°C to 121°C at 1°C / min, and cooled from 121°C to 100°C at 2°C / min. After cooling to 95°C, the flask was taken out and placed on a tray containing ultrapure water to cool for 30 minutes. After cooling, the eluate in the flask was transferred to a conical beaker. 15mL of ultrapure water was collected with a whole pipette, poured into the flask, and gently shaken to pour only the supernatant into the conical beaker. The same operation was performed twice more. The same operation was performed on the blank to obtain an eluate. 0.05 mL of methyl red was dropped into each of the sample and blank eluates. 0.02 mol / L hydrochloric acid was dropped into the sample eluate, and the amount of hydrochloric acid consumed when the eluate turned the same color as the blank was recorded, and the amount of hydrochloric acid consumed per gram of glass was calculated.
[0069] The alkali resistance was evaluated according to ISO 695 (1991). The detailed test procedure is as follows: First, a test piece with a total surface area of 15 cm2, all of whose surfaces were mirror-polished, was used. 2A glass sample was prepared, and as a pretreatment, the sample was immersed in a solution in which hydrofluoric acid (40 wt%) and hydrochloric acid (2 mol / L) were mixed in a volume ratio of 1:9, and stirred with a magnetic stirrer for 10 minutes. The sample was then taken out and ultrasonically cleaned in ultrapure water for 2 minutes three times, and then ultrasonically cleaned in ethanol for 1 minute twice. The sample was then dried in an oven at 110°C for 1 hour and cooled in a desiccator for 30 minutes. The weight m1 of the sample thus obtained was measured and recorded to an accuracy of ±0.1 mg. Next, 800 mL of a solution in which 1 mol / L sodium hydroxide aqueous solution and 0.5 mol / L sodium carbonate aqueous solution were mixed in a volume ratio of 1:1 was placed in a stainless steel container, heated to boiling using an electric heater, and the sample suspended by a platinum wire was placed in and held for 3 hours. In order to prevent the amount of liquid from decreasing during the test, the opening of the container lid was plugged with a gasket and a cooling tube. The sample was then removed and immersed three times in a beaker containing 500 mL of 1 mol / L hydrochloric acid, followed by ultrasonic cleaning in ultrapure water for one minute three times and ultrasonic cleaning in ethanol for one minute twice. The cleaned sample was then dried in an oven at 110 °C for one hour and cooled in a desiccator for 30 minutes. The weight m2 of the sample thus treated was measured to an accuracy of ±0.1 mg and recorded. Finally, the weights m1 and m2 mg of the sample before and after immersion in the boiling solution and the total surface area A cm of the sample were measured. 2 The weight loss per unit area ρ was calculated using Equation 1. [Formula 1] Weight loss per unit area ρ = 100 × (m1-m2) / A
[0070] Acid resistance was evaluated according to the method of YBB00342004-2015. The detailed test procedure is as follows. First, a sample with a total surface area of 50 cm2 with all surfaces mirror-polished was used. 2A glass sample was prepared, and as a pretreatment, the sample was immersed in a solution in which hydrofluoric acid (40 mass%) and hydrochloric acid (2 mol / L) were mixed in a volume ratio of 1:9, and stirred with a magnetic stirrer for 10 minutes. The sample was then taken out and ultrasonically cleaned in ultrapure water three times for 1 minute, and then ultrasonically cleaned in ethanol twice for 1 minute. The sample was then dried in an oven at 110°C for 1 hour and cooled in a desiccator for 30 minutes. The mass m1 of the sample thus obtained was measured and recorded to an accuracy of ±0.1 mg. Next, 800 mL of 6 mol / L hydrochloric acid was placed in a quartz glass beaker, heated to boiling using an electric heater, and the sample suspended by a platinum wire was placed in and held for 6 hours. In order to prevent the amount of liquid from decreasing during the test, the opening of the container lid was plugged with a gasket and a cooling tube. The sample was then taken out and ultrasonically cleaned in ultrapure water three times for 1 minute, and then ultrasonically cleaned in ethanol twice for 1 minute. The washed sample was then dried in an oven at 110 °C for 1 hour and cooled in a desiccator for 30 minutes. The mass m2 of the sample thus treated was measured to an accuracy of ±0.1 mg and recorded. Finally, the mass m1 and m2 mg of the sample before and after immersion in boiling hydrochloric acid and the total surface area A cm2 of the sample were measured. 2 From this, half the weight loss per unit area S was calculated using the following formula 2. [Formula 2] Half the weight loss per unit area S = 100 x (m1-m2) / (2 x A)
[0071] The Young's modulus was measured by a resonance method (JE-RT3 manufactured by Nippon Technoplus).
[0072] The thermal expansion coefficient was evaluated by using a sample machined to 20 mm×5 mmφ and measuring the average linear thermal expansion coefficient in a temperature range of 30 to 380° C. A Dilatometer manufactured by NETZSCH was used for the measurement.
[0073] The average transmittance in the wavelength range of 400 to 800 nm and the transmittance in the wavelength range of 350 nm were evaluated by measuring the transmittance in the wavelength range of 350 to 800 nm for a sample that was optically polished on both sides to a thickness of 1 mm using a spectrophotometer. A JASCO V-670 spectrophotometer was used for the measurement.
[0074] As is clear from Tables 1 and 2, in Examples 1 to 14, β-quartz solid solution was precipitated, and the glasses had excellent hydrolysis resistance and transparency, a high Young's modulus, and a thermal expansion coefficient close to 0. On the other hand, in Comparative Examples 1 and 2, the glasses were amorphous glass, consumed a large amount of hydrochloric acid, had poor hydrolysis resistance, and had a thermal expansion coefficient of 40×10 -7 The temperature was high, at over 100℃.
[0075] Example 2 Table 3 shows another example of the glass composition of the pharmaceutical container of the present invention.
[0076] [Table 3] [Industrial Applicability]
[0077] The pharmaceutical glass container of the present invention can be suitably used as a primary packaging material, a protective container, etc. for ampoules, vials, prefilled syringes, cartridges, containers for freeze-dried preparations, preparations that are easily deteriorated by ultraviolet light, etc.
Claims
1. Li 2 O-Al 2 O 3 -SiO 2 The present invention is made of a glass-ceramic material. In the crystallized glass, a β-quartz solid solution is precipitated as a main crystal, The crystallized glass contains, in weight percent, Al 2 O 3 / Li 2 O is 1 to 10, SiO 2 / Li 2 O is 5 to 18, SiO 2 / (Li 2 O+Na 2 O+K 2 O+MgO+CaO+SrO+BaO) is 12 or more, and TiO 2 A pharmaceutical glass container comprising 1 to 8% of alumina.
2. 2. The pharmaceutical glass container according to claim 1, characterized in that in a hydrolysis resistance test according to ISO 4802-1 (1988), the consumption of 0.01 mol / L hydrochloric acid per 100 mL of elution solution is 0.50 mL or less.
3. The crystallized glass contains, in weight percent, SiO 2 40-75%, Al 2 O 3 6-30%, Li 2 3. The pharmaceutical glass container according to claim 1, further comprising 0.1 to 10% O.
4. 4. The medical glass container according to claim 1, wherein the Young's modulus is 60 GPa or more.
5. Thermal expansion coefficient at 30 to 380°C is 20 x 10 -7 5. The pharmaceutical glass container according to claim 1, wherein the temperature is 0.15 to 1.5° C. or lower.
6. 6. The pharmaceutical glass container according to claim 1, which has a thickness of 1 mm and an average transmittance of 65% or more at wavelengths of 400 to 800 nm.
7. 7. The medical glass container according to claim 1, which has a thickness of 1 mm and a transmittance of 60% or less at a wavelength of 350 nm.
8. In an alkali resistance test according to ISO 695 (1991), the weight loss per unit area ρ was 75 mg / dm 2 The pharmaceutical glass container according to any one of claims 1 to 7, characterized in that:
9. A manufacturing method for obtaining the pharmaceutical glass container according to any one of claims 1 to 8, comprising the steps of: A method for producing a medical glass container, comprising the steps of: processing a glass tube to obtain a glass container; and then heat-treating the glass container to crystallize it.
Citation Information
Patent Citations
Method for storing traditional Chinese medicinal materials by microcrystalline glass
CN104495007A
Transparent crystallized glass
JP1989052631A
Li2-al2o3-sio2 based glass ceramics
JP1999228181A
Li2o-al2o3-sio2-based crystallized glass and crystalline glass
JP2001048582A
Li2O-Al2O3-SiO2-BASED CRYSTALLIZED GLASS
JP2008007398A